Kepuasan Pengunjung Berdasarkan Kualitas Pelayanan dan Fasilitas Wisata pada Objek Wisata Bukit Jaddih di Kabupaten Bangkalan - Rahmasari Tiara; Nurita Andriani (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This study aims to determine whether service quality (X1) and tourist facilities (X2) affect visitor satisfaction (Y) on Bukt Jaddih tourism in Bangkalan Regency. The research method used in this research is quantitative method with descriptive quantitative type with a population of visitors who visit Jaddih Hill tourism. The sample in this study were 100 respondents who visited Bukit Jaddih tourism. For data collection, it was carried out by distributing questionnaires. The results of this study indicate that the quality of service and tourist facilities has a positive and significant effect on the variable of visitor satisfaction in Bukit Jaddih tourism in Bangkalan Regency.